Modeling growth of mandibles in the Western Arctic caribou herd - Ver Hoef, Jay M.; Valkenburg, Patrick; Dau, James R. (Rangifer, 2001)
We compared growth curves for ramus length and diastema length from two autumn collections of mandibles of male Western Arctic Herd caribou in Alaska. We were primarily interested in determining if growth curves of caribou mandibles differed between caribou born during 1959-1967, after the herd had been high for several years and was probably declining in size, and those born during 1976-1988, when the herd was increasing in size. To compare these growth curves, we used a nonlinear model and used maximum likelihood estimates and likelihood ratio tests. We found that growth rates were similar between periods, but intercepts and variances of growth curves differed. From this we infer that calves were smaller in autumn during the 1960s and that significant compensatory growth did not occur later in life.